Hubungan Kadar Hemoglobin dan Status Gizi Pada Ibu Hamil Aterm dengan Berat Badan Lahir - Rully Fatriani (Jurnal Ilmu Gizi Indonesia (JIGZI), 2022)
AbstractThe nutritional status of pregnant women is the main factor that can predict the baby's birth weight. One that determines the growth and development of the fetus is the mother's intake of micronutrients during pregnancy. Birth weight is the weight measured shortly after the baby is born. The concentration of hemoglobin in the third trimester can increase the risk of low birth weight. This observational study with a cross-sectional design, aims to determine the relationship between hemoglobin levels and nutritional status of pregnant women with the incidence of birth weight babies. The sample in this study were 50 pregnant women who gave birth in several independent midwife practices and met the participation criteria using consecutive sampling techniques. Data were analyzed by statistical correlation test. The results showed that there was a significant relationship between the nutritional status of the mother (upper arm circumference (P=0.000)) and the baby's birth weight. Based on this study it can be concluded that the hemoglobin level of pregnant women and the nutritional status of pregnant women affect the baby's birth weight. Keywords : nutritional status, hemoglobin level, birth weight AbstrakStatus gizi ibu hamil merupakan faktor utama yang dapat memprediksi berat badan lahir bayi. Salah satu yang menentukan pertumbuhan dan perkembangan janin adalah asupan mikronutrien ibu selama masa kehamilan. Berat badan lahir merupakan berat badan yang diukur sesaat setelah bayi lahir. Konsentrasi hemoglobin pada trimester ketiga dapat meningkatkan risiko berat badan lahir rendah. Penelitian observasional dengan desain cross sectional ini bertujuan untuk mengetahui hubungan kadar hemoglobin dan status gizi ibu hamil dengan kejadian berat badan lahir bayi. Sampel dalam penelitian ini adalah sebanyak 50 ibu hamil yang melahirkan di beberapa praktik mandiri bidan dan memenuhi kriteria keikutsertaan dengan menggunakan teknik consecutive sampling. Data dianalisis dengan uji korelasi statistik. Hasil penelitian diperoleh ada hubungan yang bermakna antara status gizi ibu (Lingkar Lengan Atas (P=0,000)) dengan berat lahir bayi. Berdasarkan penelitian ini dapat disimpulkan bahwa kadar hemoglobin ibu hamil dan status gizi ibu hamil mempengaruhi berat badan lahir bayi. Kata Kunci : status gizi, kadar hemoglobin, berat badan lahir